Control and Power Management Strategy for Shunt DC Electric Spring Integrated DC Microgrid - Anu, A. G.; Harikumar, R.; Ushakumari, S. (Distributed Generation & Alternative Energy Journal, 2022)
Incorporation of intermittent renewable sources and nonlinear loads to DC microgrid (DCMG) has increased its vulnerability to voltage instability and flicker. An innovative Demand Side Management (DSM) program that can help in mitigating these voltage disruptions is the deployment of DC Electric Spring (DCES) technology. In this regard, this paper focuses on small signal modeling and controller design of shunt DCES (ShDCES) in DCMG. The test system comprises of an MPPT controlled Solar Photo-Voltaic (SPV) system, battery-operated DCES and various loads. The MATLAB / Simulink performance analysis of the system indicates that, with the incorporation of power management strategy, the ShDCES configuration has enhanced the power quality of SPV-fed DCMG with fast dynamic response in comparison with its “series” counterpart. The effective utilization of battery operated DCES on the load side, instead of the source side, makes it less battery dependent, resulting in enhancement of battery life and lesser environmental hazards. The simulation results are also validated using real-time simulator OP4510 RTS.